Effects of patient race on processes and experiences of clinical interactions in US emergency departments: A mixed-methods systematic review - Tommy J. Flynn; Bonnie Mowinski Jennings; David W. Wright; Ymir Vigfusson; Dian D. Evans; Vicki Hertzberg; Emily J. Burns; Katherine A. Yeager (PLoS ONE, 2025)
Background Evidence shows that patients identified as Black experience worse emergency department (ED) care compared to patients identified as White. Clinical interactions (CI) are thought to affect racial disparities, but no systematic reviews to date have synthesized the evidence on the effects of patient race on CI processes and experiences. Objective We synthesized evidence from published studies comparing observed and/or patient-reported CI processes and experiences between patients identified as Black and White in US EDs. Methods This was a mixed-methods systematic review following the Joanna Briggs Institute guidelines and registered a priori with PROSPERO (CRD42021281653). We used a broad search strategy to query six databases. Peer-reviewed original research reports comparing processes or experiences of CIs between Black and White patients in US EDs from 2004 to 2024 were eligible for inclusion. Results Nine studies met inclusion criteria. Of these, three focused on observational CI processes and six focused on patient-reported CI experiences. Evidence of differences in CI processes and patient-reported experiences between Black and White patients was inconclusive. We identified four themes across measures used in studies of patient reported CI experiences, however, including responsive nonverbal behavior, effective verbal communication, person centeredness, and patient satisfaction. Discussion Research on the effects of patient race on ED CIs is lacking, especially research with observed real-world CI processes. Psychometrically robust instruments and conceptual clarity in the study of racial disparities in CI experiences are needed. We provide groundwork for future research development on racial disparities in ED CIs.